Investigating the relationship between the depression levels of midwives and nurses and their emotional labor and secondary traumatic stress levels in the COVID-19 pandemic period with structural equation modelling - Yilmaz, Ayse Nur; Derya, Yesim Aksoy; Altiparmak, Suemeyye; Cihan, Emel Guclu; Oztas, Hatice Gul (W B Saunders Co-Elsevier Inc, 2022)
In this study, it was aimed to investigate the relationship between depression levels in midwives and nurses and their emotional labor and secondary traumatic stress levels in the COVID-19 pandemic process structural equation modelling. This cross-sectional study was conducted with 313 midwives and nurses. According to the model formed based on the presence of depression, as the Emotional Labor scores of the participants increased, their Beck Depression scores decreased 0.947-fold, while as their Secondary Traumatic Stress Scale scores increased, their Beck Depression scores increased 1.116-fold. It was determined that the scores of the participants in the Emotional Labor and Secondary Traumatic Stress Scales explained 42.8% of their Beck Depression Inventory scores. It was concluded that the depression statuses of the participants were affected by their emotional labor and secondary traumatic stress statuses.
Keywords: COVID-19; Depression level; Emotional labor; Secondary traumatic stress; Structural equation modelling